Mengurai Kisah Kain dan Habel dalam Pemaknaan Kaum Pentakostal - Manurung, Kosma; Wondal, Ray (Sekolah Tinggi Teologi Parakletos Tomohon, 2023)
Abstract: The story of Cain and Abel in Genesis 4:1-16 is an interesting story to study and examine because this is the story of the brotherhood of the first family in the Bible. This story also contains the story of the heinous savagery committed by Cain who was so willing to kill his only brother at that time which the Bible describes as the story of the first murder. This research intends to unravel the story of Cain and Abel in the meaning of the Pentecostals. It is hoped that the selection of a descriptive qualitative method and literature review will provide an accurate description of the colors in Adam's family, the description of the story of Cain and Abel in the Genesis 4:1-16 passage, as well as the meaning of the Pentecostals for this story. It is concluded that for Pentecostals the story of Cain and Abel is an important warning for believers to continue to maintain a personal relationship with God, an exhortation to seek and maintain harmony in the family, there are consequences for every action, and this story also talks about the legacy left behind for the next generation.Abstrak: Kisah Kain dan Habel dalam Kejadian 4:1-16 adalah sebuah kisah yang menarik untuk dikaji dan dicermati karena ini merupakan kisah persaudaraan dari keluarga pertama yang ada di Alkitab. Kisah ini juga berisikan kisah kebiadaban keji yang dilakukan oleh Kain yang begitu tega menghabisi adiknya satu-satunya waktu itu yang diterangkan oleh Alkitab sebagai kisah pembunuhan pertama. Penelitian ini bermaksud mengurai kisah Kain dan Habel dalam pemaknaan kaum Pentakostal. Pemilihan metode kualitatif deskriptif dan kajian literatur diharapkan mampu memberikan gambaran yang cermat terkait warna-warni dalam keluarga Adam, uraian kisah Kain dan Habel dalam perikop Kejadian 4:1-16, serta pemaknaan dari kaum Pentakostal terhadap kisah ini. Disimpulkan bahwa bagi kaum Pentakostal kisah Kain dan Habel ini merupakan sebuah peringatan penting bagi orang percaya untuk terus menjaga hubungan pribadi dengan Tuhan, sebuah desakan untuk mengusahakan dan memelihara kerukunan di keluarga, ada akibat untuk setiap tindakan, serta kisah ini juga berbicara tentang legacy yang ditinggalkan untuk generasi selanjutnya.